Supplementing Synbiotic in Sows' Diets Modifies Beneficially Blood Parameters and Colonic Microbiota Composition and Metabolic Activity in Suckling Piglets - Ma, Cui; Gao, Qiankun; Zhang, Wanghong; Zhu, Qian; Tang, Wu; Blachier, Francois; Ding, Hao; Kong, Xiangfeng (Frontiers in Veterinary Science, 2020)
Nutrients in the maternal diet favor the growth and development of suckling piglets and alter their gut microbiota composition and metabolic activity, thus affecting the hosts. The present study analyzed, in suckling piglets from sows receiving antibiotic or synbiotic supplements from pregnancy to lactation, several biochemical parameters, oxidative/anti-oxidative indices, inflammatory cytokines, and ingestion-related factor levels in plasma, as well as colonic microbiota composition and metabolic activity, and mucosal expression of genes related to the intestinal barrier function. Compared with the control group, maternal synbiotic supplementation decreased (P < 0.05) the plasma levels of glucose, AMM, TC, low-density lipoprotein-cholesterol (LDL-C), MDA, H2O2, ghrelin, CCK, PP, IL-1β, IL-2, IL-6, TNF-α, Ala, Cys, Tau, and β-AiBA, the levels of propionate and total short-chain fatty acids (SCFAs) in the colonic luminal content, and colonic abundances of RFN20, Anaerostipes, and Butyricimonas; while increased (P < 0.05) the plasma levels of urea nitrogen (UN), Ile, Leu, α-AAA, α-ABA, and 1-Mehis, as well as colonic abundances of Sphingomonas, Anaerovorax, Sharpea, and Butyricicoccus. Compared with the antibiotic group, maternal synbiotic supplementation decreased (P < 0.05) the plasma levels of glucose, gastrin, and Ala, as well as abundances of Pasteurella and RFN20 and propionate level in the colonic content. Expression of genes coding for E-cadherin, Occludin, ZO-1, ZO-2, IL-10, and interferon-α were down-regulated in the colonic mucosa. The synbiotic supplementation increased (P < 0.05) the plasma levels of UN, Leu, α-ABA, and 1-Mehis, the abundances of Anaerovorax, Sharpea, and Butyricicoccus and expression of genes coding for E-cadherin, Occludin, ZO-1, ZO-2, IL-10, and interferon-α. Spearman correlation analysis showed that there was a positive correlation between colonic Anaerostipes abundance and acetate and SCFAs levels; whereas a negative correlation between Fusobacteria and Fusobacterium abundances and acetate level. These findings suggest that synbiotic supplementation in the maternal diet improved nutrient metabolism and intestinal barrier permeability, reduced oxidative stress, and modified colonic microbiota composition and metabolic activity in suckling piglets.